Comparison of Quality of Life Between Fun Run and Slo-Pitch Communities in Bandung City - Haidir, Erik Dwi; gumilar, agus; Mudjihartono, Mudjihartono (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2025)
This study aimed to compare the quality of life between members of the Fun Run and Slo-Pitch sport communities in Bandung City. A cross-sectional comparative study design was employed involving 125 participants, consisting of 65 Fun Run members and 60 Slo-Pitch members, selected through purposive sampling. Quality of life was measured using the WHOQOL-BREF instrument, which assesses physical, psychological, social, and environmental domains. Data were analyzed using descriptive statistics and an independent samples t-test. The results showed that the mean quality of life score of the Fun Run community (M = 92.9) was slightly higher than that of the Slo-Pitch community (M = 91.7); however, the difference was not statistically significant (p = 0.585). These findings indicate that there is no significant difference in overall quality of life between the two communities despite differences in activity characteristics. Given the cross-sectional nature of the study, the findings should be interpreted descriptively and do not imply a causal relationship. Further studies using longitudinal or mixed-methods designs are recommended to explore the underlying mechanisms linking community-based physical activity and quality of life.